Durable Clinical Response to Pyrotinib After Resistance to Prior Anti-HER2 Therapy for HER2-Positive Advanced Gastric Cancer: A Case Report - Huang, Le-Tian; Ma, Jie-Tao; Zhang, Shu-Ling; Li, Xiao-Han; Sun, Li; Jing, Wei; Zhao, Jian-Zhu; Wang, Yan-Ru; Han, Cheng-Bo (Frontiers in Oncology, 2019)
ABSTRACT Background: Patients with advanced gastric cancer, especially the HER2-positive type, have a poor prognosis; there is a paucity of effective anti-HER2 drug therapies in patients who develop resistance to trastuzumab. Case presentation: We report the case of a 36-year-old male with HER2-positive gastric cancer with lung and liver metastases. The patient responded after treatment with trastuzumab combined with chemotherapy and attained a progression-free survival (PFS) of 17 months. Subsequently, the patient received apatinib that selectively inhibits the VEGFR2 and obtained an evident tumor response and a PFS of 8 months. When the disease progressed again, the regimen containing lapatinib failed. Then, the patient received treatment with nivolumab. However, he presented with hyper-progressive disease (HPD). Finally, he received a combination of capecitabine and pyrotinib, an irreversible dual TKI, acting on HER2 and EGFR. The tumor shrank markedly with this combination therapy. The mechanism of both HPD due to immunotherapy and the resistance to trastuzumab and lapatinib were investigated in this case. Loss of phosphatase and tensin homolog (PTEN) and new mutations of BRCA1 and KRAS were detected after resistance to trastuzumab and lapatinib. Conclusions: For patients with HER2-positive advanced gastric cancer who have developed resistance to trastuzumab, pyrotinib is a promising new agent, which can be used as salvage therapy.